Transcriptomic sequencing and differential analysis of Kazakh horse muscles from various anatomical locations - Wubulikasimu, Mierkadina·; Liu, Jiahao; Yao, Xinkui; Meng, Jun; Wang, Jianwen; Zeng, Yaqi; Li, Linling; Ren, Wanlu (Frontiers in Veterinary Science, 2025)
Kazakh horses, a distinguished breed in China known for their dual-purpose use in milk and meat production, exhibit early maturation, tolerance to coarse feeding, and strong resistance to environmental stress. However, the gene expression differences across various muscle tissues of Kazakh horses have yet to be elucidated. In this study, transcriptomic sequencing was performed on muscle tissues from three anatomical regions of Kazakh horses, including the longissimus dorsi (Gb), external oblique (Gf), and diaphragm (Gg) muscles. In the Gb and Gf groups, 426 differentially expressed genes (DEGs) were identified, including TPM1, TNNI2, ACTN3, and MYH8, of which 147 were upregulated and 279 downregulated. In the Gf and Gg groups, 1,762 DEGs were detected, including MYBPH, SLC39A8, EMX2, and GRB7, with 1,391 upregulated and 371 downregulated. Additionally, 644 DEGs were identified between the Gg and Gb groups, including HOXD9, TBX1, LDHA, and PKM, with 172 upregulated and 472 downregulated. GO annotation and KEGG enrichment analysis revealed that the DEGs, such as TPM1, TNNI2, ACTN3, and MYH8, were primarily involved in System Development, Extracellular Space, and Protein-Arginine Deiminase Activity. Furthermore, pathways related to skeletal muscle growth, including Cytoskeleton in Muscle Cells, Cytokine-Cytokine Receptor Interaction, and Motor Proteins, were significantly enriched. RT-qPCR analysis validated the accuracy of the transcriptomic sequencing data. This study provides valuable insights into the differential expression of genes and related signaling pathways in various muscle tissues of Kazakh horses, rendering a theoretical foundation and data references for understanding skeletal muscle growth and improving meat production in equines.